Insights Into the Hypometabolic Stage Caused by Prolonged Starvation in L4-Adult Caenorhabditis elegans Hermaphrodites - Carranza-García, E.; Navarro, Rosa E. (Frontiers in Cell and Developmental Biology, 2020)
Animals alter their reproductive cycles in response to changing nutritional conditions, to ensure that offspring production only occurs under favorable circumstances. These adaptive strategies include reversible hypometabolic states of dormancy such as “arrest” and “diapause.” The free-living nematode Caenorhabditis elegans can arrest its life cycle during some larval stages without modifying its anatomy and physiology until conditions improve but it can also modify its morphological and physiological features to cope with harsh conditions and transition into diapause. The well-defined “dauer” diapause was described more than 40 years ago and has been the subject of comprehensive investigations. The existence of another hypometabolic state, termed adult reproductive diapause (ARD), has been debated after it was first described 10 years ago. Here, we review the current knowledge regarding the effect of food deprivation during the pre-reproductive larval and adult stages on overall organismal homeostasis, highlighting the implications on germ cell maintenance and fertility preservation.